Basal plane stacking faults in semipolar AlGaN: Hints to Al redistribution. Issue 11 (24th July 2014) - Tischer, Ingo; Frey, Manuel; Hocker, Matthias; Jerg, Lisa; Madel, Manfred; Neuschl, Benjamin; Thonke, Klaus; Leute, Robert A.R.; Scholz, Ferdinand; Groiss, Heiko; Müller, Erich; Gerthsen, Dagmar
<x xml:space="preserve">Abstract</x> We investigate the optical and structural properties of an AlGaN layer with low Al content grown on a <alternatives><inline-graphic mimetype="image" xlink:href="ark:/27927/pgh2cktsdx5" xlink:type="simple" xmlns:xlink="http://www.w3.org/1999/xlink" />11‾01</alternatives> semipolar GaN facet. The correlation of scanning transmission electron microscopy with high‐resolution cathodoluminescence recorded on the identical sample spot allows to identify the emission features of AlGaN defects. We assign a basal plane stacking fault of <alternatives><inline-graphic mimetype="image" xlink:href="ark:/27927/pgh2cktsfgh" xlink:type="simple" xmlns:xlink="http://www.w3.org/1999/xlink" />I1</alternatives> type to a spatially localized emission <alternatives><inline-graphic mimetype="image" xlink:href="ark:/27927/pgh2cktsffz" xlink:type="simple" xmlns:xlink="http://www.w3.org/1999/xlink" />80meV</alternatives> below the (<alternatives><inline-graphic mimetype="image" xlink:href="ark:/27927/pgh2cktsfcv" xlink:type="simple" xmlns:xlink="http://www.w3.org/1999/xlink" />D0X)</alternatives> in AlGaN. This defect starts inside the GaN template and continues through the AlGaN layer. The energy spacing between the (<alternatives><inline-graphic mimetype="image" xlink:href="ark:/27927/pgh2cktsfb9" xlink:type="simple" xmlns:xlink="http://www.w3.org/1999/xlink" />D0X</alternatives>) related emission band and the corresponding <alternatives><inline-graphic mimetype="image" xlink:href="ark:/27927/pgh2cktsf9r" xlink:type="simple" xmlns:xlink="http://www.w3.org/1999/xlink" />I1</alternatives>‐type basal plane stacking fault emission is larger than in the binary GaN case which indicates a modified Al content at the defect.